Avoiding Archaeological Disasters : Risk Management for Heritage Professionals. - Stapp, Darby C. (Techniques & Issues in Cultural Resource Management, 2., 2009)
This book is for project engineers and managers, government staff and consultants to help avoid unforeseen archaeological problems in construction and development projects.